Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.